Perbandingan Kualitas Layanan Dua Aplikasi Transportasi Online Menggunakan Metode Servqual - Fransiska Prihatini Sihotang (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
Internet has become something that was needed by most people in Indonesia. Nowdays, Internet was used by people not only just as a tool to help their work, but also as a lifestyle such as accessing the news, using a social media, online shopping or even online transportation. There werw so many companies provide an online application-based services, which is one of many reason that causes competition between companies. To maintain customer loyalty, company have to ensure that the aplication services that provided were higher or at least met the customer perceptions. This study aims to determine whether the application services quality that provided by PT ABC and XYZ Pte. Ltd. is already met the customer expectations. Servqual method that consist of five dimensions of measurement such as tangible, reliability, responsiveness, assurance, and empathy was used in this study with questions tailored to electronic services. The result of this study showed that the Application of PT ABC and XYZ Pte. Ltd. Was not provided a service quality that met the customer expectations yet. All dimensions of measurement show that customer expectations was higher than customer perceptions. The dimensions of Assurance in both researched application is the top second biggest gap on both of the data analized. This indicated that customers expect a better security from both applications which has not been fulfilled by the application provider company yet